2018
DOI: 10.1111/mcn.12719
|View full text |Cite
|
Sign up to set email alerts
|

Can community health workers manage uncomplicated severe acute malnutrition? A review of operational experiences in delivering severe acute malnutrition treatment through community health platforms

Abstract: Community health workers (CHWs) play an important role in the detection and referral of children with severe acute malnutrition (SAM) in many countries. However, distance to health facilities remains a significant obstacle for caregivers to attend treatment services, resulting in SAM treatment coverage rates below 40% in most areas of intervention. The inclusion of SAM treatment into the current curative tasks of CHWs has been proposed as an approach to increase coverage. A literature review of operational exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…The results of this study show that increased anthropometric measurements at admission are directly associated with an increased probability of being cured after treatment. The combination of early treatment and close follow-up due to the proximity of CHWs performing integrated management of childhood diseases could be the reason for the high effectiveness of iCCM+ interventions compared to the treatment provided at health centers [9]. Furthermore, the recovery rate achieved by CHWs in this study (95.5%) was the highest of all the iCCM+ experiences published to date, which range from 60.0% in India to 93.8% in Angola [8,43].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The results of this study show that increased anthropometric measurements at admission are directly associated with an increased probability of being cured after treatment. The combination of early treatment and close follow-up due to the proximity of CHWs performing integrated management of childhood diseases could be the reason for the high effectiveness of iCCM+ interventions compared to the treatment provided at health centers [9]. Furthermore, the recovery rate achieved by CHWs in this study (95.5%) was the highest of all the iCCM+ experiences published to date, which range from 60.0% in India to 93.8% in Angola [8,43].…”
Section: Discussionmentioning
confidence: 69%
“…Since 2010, efforts have been made to add SAM treatment to the curative tasks that CHWs can provide close to families, referred to as the iCCM+ approach. A review of the operational experiences of this approach has recently been published [9] and shows that programs implementing this new community approach can achieve better outcomes in terms of recovery and defaulter rates than standard CMAM programs performed at HFs far away from the affected villages. This review also found that the iCCM+ model could potentially double the coverage of SAM treatment services, achieving over 80% treatment coverage in a cost-effective manner, reducing the time and money that the families would expend to treat their children at the health centers, which are usually located far away from their households [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stock out of key commodities (i.e. RUTF) is a key challenge affecting performance [18,19] and contributes to poor compliance which in turn have a negative impact on effectiveness of the nutrition program [20]. There is often enough RUTF at country/regional level but the situation in the field can be very different; related to challenges with logistics/distribution of supplies [15].…”
Section: Discussionmentioning
confidence: 99%
“…SAM is continuing to be the major public health problem and an essential contributor to morbidity and mortality in under-five children [4,5]. In interventions taken by community health workers, a recovery rate of around 90% was estimated in a systematic review and meta-analysis done in middle-and low-income counties [6]. A study done in Asian and African countries reported that recovery rates from SAM ranges from 25% to 95% at inpatient management and 50% to 93% at outpatient management program [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%